O trabalho cotidiano de profissionais de um serviço de atendimento móvel de urgência - Hanna Beatriz Bacelar Tibaes (2017)
The Brazilian health system presents high morbidity and mortality related to urgencies, configured over the years as a critical area in the Unified Health System (SUS). The organization of the Emergency Care Network through regionalization is a strategy to overcome the fragmentation of health services and to qualify care management. In thiscontext, SAMU is one of the components of prehospital care with an important contribution in the treatment of acute, chronic and acute complications and in the complex expansion of external causes. The objective of this study was to understand the daily work of healthprofessionals and managers of SAMU Macro Norte de Montes Claros. This is a qualitative study, outlined by the research strategy Case Study based on Comprehensive Sociology of Daily Life. The scenario of the study was the SAMU Macro Norte, operational base of Montes Claros. For data collection, three sources of evidence were used, these being, secondary data analysis; interview with semi-structured script and direct observation. Secondary data were obtained from October to December 2015, using the database provided by the SAMU Macro Norte statistic sector for the periods from 2013 to 2015. Qualitative data were collected from November 2015 to January Of 2016 and obtained through a semistructured interview, as well as direct observation, with forty-one professionals, managers, nurses, doctors and nursing technicians. For the analysis of the data was used the Content Thematic Analysis. The research was analyzed and approved by the Committee of Ethics inResearch of Human Subjects with CAAE Opinion nº 50185515.4.0000.5149. Secondary data was analyzed in Microsoft Office Excel 2007 using descriptive statistics and presented as absolute, percent, and averages. From the analysis emerged the theme "Service profile of the Mobile Emergency Care Service in the North of Minas Gerais". The results of the interview and observation data pointed to two categories: "The historical construction of SAMU in the North of Minas Gerais, Brazil: from conception to regionalization" and "Another look at thedaily work of professionals from the Mobile Assistance Service Of Urgency. The results were organized into one theme and two categories and presented in three articles. This study allowed us to describe the service profile of the SAMU in the North of Minas Gerais and tounderstand the daily work through different perspectives of those who perform it, as well as the influence of the environment on the actors involved, the behavior, the relations and the ways of Do the care, revealing particular and hidden aspects of the work. The work iscomplex, permeated by singularities and presents many unpredictable and unusual situations making care and care provided to the patient differentiated. The subjectivity is present in everyday life at all times and the professionals reveal feelings about the work and the care given to the patient. It was observed the multiplicity of collective experiences based on the banal relations of the day to day of the teams, through a collective effort that integrates the daily work of SAMU. Thus, the "invisible side" of the work was captured, which, articulated with the prescribed one, gives new meanings to the work. It is hoped that this study may promote the reflection of the subjects involved in this activity, raise new questions, generate new discussions and research on the subject and collaborate with health systems that seek, in the regionalization, improvements for the services offered to the population.